THE STUDENTS’ IMPLEMENTATION OF ETIQUETTE IN TABLE MANNERS PROGRAM - Rahayu, Pipit; Eripuddin, Eripuddin; Ng, Yu Jin; Kharisma, Putri; Bunda, Ridho Harapan (Universitas Putera Batam, 2025)
This study aims to analyze the implementation of student etiquette in a program that teaches the rules of manners in the context of communal dining. Table etiquette is an essential part of social and professional life, and these skills are expected to enhance students' self-image and interpersonal abilities. The research method involved distributing questionnaires and conducting interviews with 7th-semester students who participated in the program. The findings indicate that the majority of 7th-semester students were able to apply etiquette well, although some challenges were observed in understanding and practicing more complex rules. Factors affecting the success of etiquette implementation include the level of understanding, cultural background, and the influence of instructors. This study recommends the need for a more structured approach and a variety of teaching methods to improve the effectiveness of the Table Manner program for 7th-semester students.